Different types of allospecific CTL clones identified by their ability to recognize peptide loading-defective target cells. - Aosai, F; Ohlen, C; Ljunggren, H; Höglund, P; Franksson, L; Ploegh, H; Townsend, A; Kärre, K; Stauss, H (1991)
Allospecific immune responses against the MHC of another individual are remarkably strong, due t a high number of responding T cell clones. Although it has been demonstrated that some allospecific cytotoxic T lymphocytes (CTL) recognize peptides presented by allogeneic MHC class I molecules, it has remained unclear whether MHC molecules can be recognized directly. We used the H-2b-derived murine lymphoma mutant RMA-S, which has a defect affecting peptide loading of class I molecules, to test whether recognition by allospecific CTL always requires the presence of peptides. Three types of anti-H-2Kb CTL clones can be distinguished by their ability to lyse RMA-S target cells. Type A CTL clones efficiently lyse these target cells, the lysis by type B CTL clones is inefficient, and type C clones fail to lyse RMA-S. Up-regulation of the levels of H-2Kb density improved lysis by type B clones, but did not lead to lysis by type C clones. Some type A and B CTL clones apparently can recognize class I molecules devoid of peptides, while others are likely to recognize peptides which are not affected by the presentation defect of RMA-S. We suggest that type C clones are specific for peptides which are not presented by the mutant cells. The results show that the majority of alloreactive CTL recognize peptide/MHC complexes, while some CTL behave as if they can recognize class I molecules in the absence of MHC-bound peptides.